Aparatus Kekuasaan Dalam Kebijakan PeduliLindungi (Jurnal Nawala Politika, 2022)
This study describes the workings of the power apparatus in implementing the PeduliLindungi policy on Kuta Beach. The apparatus of power in the process of implementing the PeduliLindungi Policy dominates the community through narratives of compliance with the policies that have been planned with the hope that the community will be easily regulated with the aim of breaking the chain of the spread of the virus. Kuta. This study uses a qualitative method to obtain data by conducting interviews and observations. This study uses the State Apparatus theory from Louis Althusser by categorizing two important elements, namely the Repressive State Apparatus and the Ideological State Apparatus. The PeduliLindung policy runs because of the continuous efforts to domination so that traders inevitably submit because their interests are still based on economic ideology. The health narrative becomes more dominant than the economic narrative even though it includes resistances.